The State of Art on the Steiner Ratio Value in R³ - Mondaini, R.; Oliveira, N.V. (Trends in Computational and Applied Mathematics, 2004)
Our aim in this work is to make a brief review of the results related to the search of the Infimum and Supremum Values of the Steiner Ratio for point sets in R3. We show the fundamental achievements which were obtained in a research period of 35 years. We also comment on a recently proposed new upper bound value which is an improvement of Smith and Mac Gregor Smith’s bound.